A costatis approach to business sustainability in turbulent environments from 2008 to 2014 - Santos, António Duarte (2019)
European countries continue to differ considerably from one another economically, not only in economic growth assessed by GDP growth rates but also in their companies' population by Economic Activities. Nonetheless these regular differences, the occurrence of crisis and other economic events can promote economic turbulence conducing to different responses, conditioned by each country's specificities. The occurrence of the 2008 financial crisis, the subsequent economic and sovereign debt crisis introduced additional factors of turbulence in the business sustainability of the European (EU) companies. This research, supported by the COSTATIS method, analyses the co-structure and measures the discrepancy between the population of EU companies for each NACE and the GDP components in their dynamics from 2008 to 2014. The results detected greater discrepancies between the population of companies and the stability of economic growth for a subset of EU countries with particularities regarding their NACE and GDP components.